Genetics of Early Onset Restless Legs Syndrome - J Gordon Millichap (Pediatric Neurology Briefs, 2008)
Linkage analysis was performed in a four-generational German family with restless legs syndrome (RLS) affecting 15 of 37 family members, in a study at the University of Lubeck, Germany.